Integration of miRNA-lncRNA-mRNA profiles in liver tissue from EpCAM knockout mice - Lei, Zili; Lei, Yuting; Chen, Guibin; Liu, Shaomin; Liu, Wanwan; Huang, Li; Yang, Lanxiang; Wu, Huijuan; Yang, Yanhong (Archives of Biological Sciences, 2022)
Paper description: Epithelial cell adhesion molecule (EpCAM) is highly expressed in the liver during development and disease, however, its role in development and liver pathology is unclear. Liver tissues of EpCAM-/- and WT mice at P0 stage were collected for RNA sequencing. Hepatic expression of miRNAs, lncRNAs and mRNAs was confirmed by qPCR. Comprehensive miRNA, lncRNA and mRNA expression profiles in EpCAM-/- mice were established, indicating that EpCAM plays important roles in liver glucose and lipid metabolism. These results will help to elucidate functions and mechanisms of EpCAM in liver development and diseases. Abstract: The epithelial cell adhesion molecule (EpCAM) is highly expressed in the liver during development and diseases. However, its role in the development and pathology of liver remains to be explored. The liver tissues of EpCAM-/- and wildtype (WT) mice at P0 stage were used for RNA sequencing. The differently expressed miRNAs, lncRNAs and mRNAs were selected and confirmed by qPCR. The expression of metabolism-related gene SET domain bifurcated 2 (Setdb2) was significantly increased in the liver of EpCAM-/- mice; the triglyceride (TG) and total cholesterol (TC) levels in the liver were also markedly decreased in EpCAM-/- mice. The microRNA (miRNA)-long noncoding RNA (lncRNA)-mRNA regulatory networks indicated that EpCAM may play important roles in glucose and lipid metabolism of the liver during development and in disease. The comprehensive miRNA, lncRNA and mRNA expression profiles in the developing liver of EpCAM-/- mice established here might help to elucidate functions and mechanisms of EpCAM during development and in diseases of the liver.